The role of migraine headache severity, associated features and interactions with overweight/obesity in inhibitory control. (2nd January 2018) - Galioto, Rachel; O'Leary, Kevin C.; Gunstad, John; Thomas, J. Graham; Lipton, Richard B.; Pavlović, Jelena M.; Roth, Julie; Rathier, Lucille; Bond, Dale S.
ABSTRACT: Aim of the Study: While migraine and obesity are related and both conditions are associated with reduced executive functioning, no study has examined whether obesity exacerbates executive dysfunction in migraine. This cross-sectional study examined whether overweight/obesity moderated associations of migraine severity and associated features with inhibitory control, one aspect of executive function. Materials and Methods: Women ( n = 124) aged 18–50 years old with overweight/obesity body mass index (BMI) = 35.1 ± 6.4 kg/m 2 and migraine completed a 28-day smartphone-based headache diary assessing migraine headache severity (attack frequency, pain intensity) and frequency of associated features (aura, photophobia, phonophobia, nausea). They then completed computerized measures of inhibitory control during an interictal (headache-free) period. Results: Participants with higher migraine attack frequency performed worse on the Flanker test (accuracy and reaction time; p < .05). Migraine attack frequency and pain intensity interacted with BMI to predict slower Stroop and/or Flanker Reaction Time (RT; p < .05). More frequent photophobia, phonophobia and aura were independently related to slower RT on the Stroop and/or Flanker tests ( p < .05), and BMI moderated the relationship between the occurrence of aura and Stroop RT ( p = .03). Conclusions: Associations of migraine severity and presence of associated features with inhibitory control varied by BMI in overweight/obese women with migraine. These findings warrant consideration of weight status in clarifying the role of migraine in executive functioning.